Pengaruh Celebrity Endorsement Terhadap Keputusan Pembelian Melalui Brand Image Skincare Nature Republic - Virgo Simamora; Rana Sadilah (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
This study has the main objectives, namely to inform the effect of celebrity endorsement on the brand image of Nature Republic skincare, to inform the influence of celebrity endorsement on the purchasing decision of Nature Republic, to inform the influence of brand image on the purchasing decision of Nature Republic, and to inform the influence of celebrity endorsement on purchasing decisions through brand image skincare Nature Republic. The sampling technique used is non-probability sampling. To determine the number of sample respondents using purposive sampling technique, the sample obtained is 100 respondents using Nature Republic. The data analysis technique needed in this research is Structural Equation Modeling (SEM) with PLS (Partial Least Square) software. The results of the analysis obtained in this study are that each variable has a positive effect on each other.Keywords: Celebrity Endorsement, Purchase Decision, Brand Image